Comparison of Alshad Ahmad's Reporting Framing on Media Kompasiana and Okecelebrity - Inayatul Aulia (Jurnal Komunikasi, 2023)
The development of technology has brought many changes to human life, such as the development of media with  various features and purposes. Youtube media, for example, there is a lot of diverse content that can be the choice  of the audience. One of them is content that discusses education and animal care, such as Alshad Ahmad's famous  YouTube content. But behind the popularity of the content, it turns out that there are people who think that the  content contains elements of animal exploitation. In addition to the development of the YouTube media, the news  media has also experienced developments, namely the presence of online news media. Of course, every media  tries to spread news that is interesting to the public. Kompasiana and Okecelbrity are the two media outlets  reporting on the figure of Alshad Ahmad. This study uses a qualitative research method with a framing analysis  model that refers to the Zhongdang Pan Kosicki model. The purpose of this study was to find out how framming  was carried out by kompasiana and okecelebrity in reporting Alshad ahmad. The results of this study describe  how the framming differs from Kompasiana and Okecelebrity media in reporting Alshad Ahmad. Alshad's framing  at Kompasiana has more to do with the issue of publicity (who) which also focuses on elements (what), namely  the trending event of Alshad Ahmad's number 1 content on YouTube during his 7 years of work. Meanwhile,  Alshad's framing in Okecelebrity has more to do with the issue of reporting on the persona (who) which also  focuses on the element (why) which has even been included in the news headlines.